Measuring kindergarteners’ motivational beliefs about writing: a mixed-methods exploration of alternate assessment formats - Takada, Megumi E.; Lemons, Christopher J.; Balasubramanian, Lakshmi; Hallman, Bonnie T.; Al Otaiba, Stephanie; Puranik, Cynthia S. (Frontiers in Psychology, 2023)
There have been a handful of studies on kindergarteners’ motivational beliefs about writing, yet measuring these beliefs in young children continues to pose a set of challenges. The purpose of this exploratory, mixed-methods study was to examine how kindergarteners understand and respond to different assessment formats designed to capture their motivational beliefs about writing. Across two studies, we administered four assessment formats — a 4-point Likert-type scale survey, a binary choice survey, a challenge preference task, and a semi-structured interview — to a sample of 114 kindergarteners engaged in a larger writing intervention study. Our overall goals were to examine the benefits and challenges of using these assessment formats to capture kindergarteners’ motivational beliefs and to gain insight on future directions for studying these beliefs in this young age group. Many participants had a difficult time responding to the 4-point Likert-type scale survey, due to challenges with the response format and the way the items were worded. However, more simplified assessment formats, including the binary choice survey and challenge preference task, may not have fully captured the nuances and complexities of participants’ motivational beliefs. The semi-structured interview leveraged participants’ voices and highlighted details that were overlooked in the other assessment formats. Participants’ interview responses were deeply intertwined with their local, everyday experiences and pushed back on common assumptions of what constitutes negatively oriented motivational beliefs about writing. Overall, our results suggest that kindergarteners’ motivational beliefs appear to be multifaceted, contextually grounded, and hard to quantify. Additional research is needed to further understand how motivational beliefs are shaped during kindergarten. We argue that motivational beliefs must be studied in context rather than in a vacuum, in order to work toward a fair and meaningful understanding of motivational beliefs about writing that can be applied to school settings.